CONSUMER ATTITUDE TOWARDS ONLINE SHOPPING AMONG INTERNATIONAL STUDENTS IN MALAYSIA - Novandi Nasty Sandya; Widya sari; Christin Agustina Purba (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This paper aims to investigate the consumer attitude towards online shopping, specifically studying the factors influencing consumers to shop online. This resarch using quantitative analysis. The data was collected from a survey through questionnaire, which were distributed through google form. The sample was randomly selected to answer a questionnaire to determine the factor influencing consumers to shopping online. Specifically, this sample are focus on indonesian students in Malaysia. The survey questionnaires were coded and analyse by using the statistical package for Social Sciences (SPSS 22.0). Two statistical techniques were used: (1) Descriptive statistics that consisted of frequency descriptions and means; and (2) Reability Test and (3) Inferential statistics that included correlations